Silakbo: A short audio documentary - Goyena, Denise Audrey Lacerna (Animo Repository, 2021)
This thesis project is a 10-minute audio documentary about an upcoming band, LxJ, and it revolved on how they made themselves known in the local music scene and how much they were willing to do to reach their passion for music. The finished audio documentary covered how a band worked when they performed in gigs, how they acquired gigs to earn income for their band expenses, as well as how they marketed themselves to the public to gain a listening audience. Furthermore, it also covered their chemistry as a band and how they work together in creating new songs as well as rehearsing together. We also showed that as a start-up band, it was not always easy for them as they did not have enough resources and connections that would let them be able to perform in front of an audience. Because of the current situation which involved COVID-19, adjustments were made to the production of this project. The researchers interviewed their subjects via Zoom and instead of a video documentary, they worked an audio documentary, accompanied with a film poster.